Enhancing Consumer Attitude Toward Culturally Mixed Symbolic Products from Foreign Global Brands in an Emerging-Market Setting: The Role of Cultural Respect. Issue 3 (September 2019) - Guo, Xiaoling; Heinberg, Martin; Zou, Shaoming
The extant literature has not examined the conditions that govern integrative and exclusionary reactions to cultural hybrid products with sufficient detail. Within an emerging-market setting, this study explores how culturally mixed symbolic products (CMSPs) from foreign global brands can avoid antagonistic consumer attitudes. Building on social categorization theory, the authors argue that foreign global brands are viewed as belonging to an out-group and may thus encounter difficulties in tapping local cultural capital, resulting in a negative relationship between brand globalness and consumer attitude toward CMSPs. However, they contend that product category moderates this relationship such that there is a stronger negative effect for nonfood products than for food products. Moreover, the authors theorize that (1) cultural respect by foreign global companies directly enhances consumer attitudes toward CMSPs and (2) cultural respect attenuates the negative brand globalness–CMSP attitude link. These hypotheses are tested using a representative consumer sample from eight provinces/municipalities in China (n = 646). Results provide important implications for global companies on how to benefit from local cultural resources in their localization processes.